The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1159/000241192
|View full text |Cite
|
Sign up to set email alerts
|

Single Injection Clearance in the Neonate

Abstract: The single injection clearance of inulin was compared to the standard clearance in neonates aged 1–20 days. In the first 3 days of life, the single injection method overestimated glomerular filtration rate by approximately 30%. From the 2nd week of life, values obtained by the two techniques were not significantly different. We conclude that caution should be paid when interpreting results obtained by the single injection technique during the very first days of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
1
1
0
2
Order By: Relevance
“…Only in a few patients trustworthy results can be obtained by this technique. These data are in accordance with those of Fawer et al [13].…”
Section: Discussionsupporting
confidence: 94%
“…Only in a few patients trustworthy results can be obtained by this technique. These data are in accordance with those of Fawer et al [13].…”
Section: Discussionsupporting
confidence: 94%
“…This finding was ascribed to the slow rate of inulin diffusion into the extracellular space of neonates. Using the 24-h inulin infusion method as a reference value, the same author found that the single-injection method correlated poorly with GFR when the single-injection clearance was estimated over 2 h. Similarly, in 1979, Fawer et al showed that the single-injection inulin technique overestimated the urinary clearance of inulin by up to 30% in the first week of life [21].…”
Section: Significance and Generalizabilitymentioning
confidence: 97%
“…Zusätzlich zur verminderten renalen Konzentrationsfähigkeit ist auch die glomeruläre Filtrationsfähigkeit der Niere sowie die tubuläre Rückresorption und die Cl – - und H + -Ionen-Elimination im Vergleich zu älteren Kindern geringer 8 . Dies erfordert ein vergleichsweise hohes Flüssigkeitsvolumen zur Ausscheidung von harnpflichtigen Substanzen.…”
Section: Physiologische Besonderheiten Frühgeborener Mit Auswirkung A...unclassified